Consumer categorization of the emerging clean meat market - Tiaga, Jacqueline (2018)
One of the most significant causes of the growing climate change crisis and a major user of water, land, and energy resources is the conventional mass production of meat. Hence, more sustainable alternatives for meat production are being explored. Clean meat, or meat developed with stem cell technology, has been proposed as a possible solution due to its expected benefits for the environment, food availability and animal welfare. To successfully introduce this product to the market, it is vital that companies producing it are aware of respective consumer acceptance and what they can do to improve it.